Modelling the Ultimate Absurdity: A Comment on "A Quantitative Study of the Strategic Arms Race in the Missile Age" - Desai, Meghnad; Blake, David (The Review of Economics and Statistics, 1981)
Meghnad Desai, David Blake, Modelling the Ultimate Absurdity: A Comment on "A Quantitative Study of the Strategic Arms Race in the Missile Age", The Review of Economics and Statistics, Vol. 63, No. 4 (Nov., 1981), pp. 629-632